2022
DOI: 10.3389/fcimb.2022.883798
|View full text |Cite
|
Sign up to set email alerts
|

Accurate 16S Absolute Quantification Sequencing Revealed Vaginal Microecological Composition and Dynamics During Mixed Vaginitis Treatment With Fufang FuRong Effervescent Suppository

Abstract: BackgroundThe diagnosis and treatment of mixed vaginitis are more complicated than single pathogenic infections, and there may be adverse reactions and several contraindications to conventional antibiotic therapy. Therefore, this study aimed to evaluate the preliminary effects of Fufang Furong Effervescent Suppository for the management of aerobic vaginitis (AV) mixed with bacterial vaginosis (BV) using Accurate 16S absolute quantification sequencing (Accu16S).MethodsIn the present randomized, blind, multi-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Because of the high proportion (68.51%) of AV patients combined with the other vaginitis in this study, and mainly combined with BV, we suggest that different pathogens influenced each other, which may have affected the interpretation of their correlation. Increasingly, studies have shown a higher incidence of AV-related mixed vaginitis (30,31), and the relationship between AV itself and HPV infection requires further investigation. Previous studies have shown that the prevalence of HR-HPV is higher in patients with BV (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high proportion (68.51%) of AV patients combined with the other vaginitis in this study, and mainly combined with BV, we suggest that different pathogens influenced each other, which may have affected the interpretation of their correlation. Increasingly, studies have shown a higher incidence of AV-related mixed vaginitis (30,31), and the relationship between AV itself and HPV infection requires further investigation. Previous studies have shown that the prevalence of HR-HPV is higher in patients with BV (32).…”
Section: Discussionmentioning
confidence: 99%
“…DNA from cervical cells was extracted for hybridization and color development. A total of 15 high-risk HPV (16, 18,31,33,35,39,45,51,52,53,56,58,59, 66, and 68) and 6 low-risk HPV (6,11,26,73,81, and 82) types can be detected by HPV-DNA detection kit provided by Jiangsu Shuoshi Biotechnology Co., Ltd. The evaluation and diagnosis results were classified into (1) "HPVpositive": one or more of the above-mentioned HPV subtypes were detected and divided into "HPV16/18-positive group" and "HPV other subtype positive group"; and (2) "HPV-negative": none of the above HPV subtypes were detected.…”
Section: Testing and Diagnosismentioning
confidence: 99%
“…Meng Li et al. investigated the effect of Fufang FuRong Effervescent Suppository on vaginal microecological composition and dynamics in mixed vaginitis(M. Li et al., 2022 ). Similar to BCFYQ , both products are vaginal suppositories derived from traditional Chinese medicine and both contain Sophora flavescens and Stemona japonica .…”
Section: Discussionmentioning
confidence: 99%